2017
DOI: 10.1002/smi.2737
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and depressive symptoms in teachers: Factor structure and construct validity of the Maslach Burnout inventory‐educators survey among elementary and secondary school teachers in Hungary

Abstract: This study validated the Hungarian version of the Maslach Burnout Inventory-Educators Survey on a sample of n = 211 elementary and secondary teachers. To test factorial validity, we ran a series of confirmatory analysis with eight models. The best fitting model was the bifactor model with general burnout and three specific factors: emotional exhaustion, depersonalization, and personal accomplishment. Analyzing the covariates revealed that gender and age were not associated with burnout, but depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 64 publications
6
51
0
13
Order By: Relevance
“…In recent years, scholars have paid more attention to the phenomenon of job burnout in different occupational groups. Previous studies on job burnout mostly focus on teachers, medical staff, police, civil servants, and other occupational groups [32,33]. There is relatively little research on the special occupational group of copper and nickel miners.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scholars have paid more attention to the phenomenon of job burnout in different occupational groups. Previous studies on job burnout mostly focus on teachers, medical staff, police, civil servants, and other occupational groups [32,33]. There is relatively little research on the special occupational group of copper and nickel miners.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher' daily work includes several demands and difficulties (Aloe et al, 2014 ). For example, large classes, pupils' complex learning needs, low social support, dysfunctional interactions with colleagues, perceived expectations to care for others in a prosocial way (Santavirta et al, 2007 ; Szigeti et al, 2016 ; Gray et al, 2017 ). Teachers may also be exposed to threats and even violence by students and/or their parents (De Cordova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One such differential demand, which may explain individual differences in teachers' psychological functioning (Klusmann et al, 2008 ), is emotionally challenging social interactions. For example, prosocial extra-role performance implying perceived expectations to care for others, e.g., students, colleagues and pupils' parents, in a prosocial way (Santavirta et al, 2007 ; Szigeti et al, 2016 ; Gray et al, 2017 ). Increased prosocial extra-role performance may be associated with better mental health (Simbula and Guglielmi, 2013 ; Lam et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some factors have been reported to influence the MBI psychometric proprieties including sample characteristics (32) and the presence or absence of burnout (33). Recently, two studies reported the best fit for a bifactor model, composed by a general factor and the three traditional factors (5, 34). In the bifactor model, the items may load simultaneously on a global burnout factor and on the three specific ones (i.e., depersonalization, emotional exhaustion and personal accomplishment).…”
Section: Introductionmentioning
confidence: 99%